Second language teachers’ sense of self-efficacy: A construct validation - Ramin Akbari (Teaching English Language, 2010)
While teacher efficacy is a well-researched concept in mainstream teacher education, it is relatively unexplored in second language (L2) teaching contexts. Part of the problem stems from lack of a specific instrument for measuring teacher efficacy in L2 settings. The present study was conducted, therefore, to develop such an instrument. “Teachers’ Sense of Efficacy scale” (TSES) formed the basis for the development of the new instrument. 35 L2 teachers with more than 3 years of experience were interviewed on the specifics of efficient foreign language teaching. After the content analysis of the interviews, ten items were developed and added to TSES. The resultant 33- item questionnaire, “Second Language Teacher Efficacy Scale”, SLTES, was administered to 272 English language teachers for construct validation. Factor analysis of the collected data with principal axis factoring yielded the same factor structure of TSES, that is, efficacy in instructional strategies, efficacy in student engagement, efficacy in classroom management which were redefined in light of the items added to each.